Modified Kyowa hydroponic system : technical and economic suitability under Malaysian conditions - Bardaie, Mohd. Zohadie; Daud, Mohamed (1985)
Hydroponic system is a highly effective plant production method. The system was developed based upon the idea that plant has a substantial ability to produce. However, in the natural environment, plant productivity is basically dependent upon its growth and development which are in turn regulated by a variety of factors. Environment factors such as light, temperature and nutritional conditions can possibly be controlled to produce a full physiological activity of plants within a certain limit. In conventional field cultivations, the maximum potential activity which plants are supposed to possess is not accomplished. This is mostly due to the lack of the growth of plant root system. As it is well known, the more the root grows, the more the plant can absorb nutritional elements and water, as long as the supply is adequate. This will result in more shoot growth culminating in a tremendous increase in plant productivity. The main feature of the Japanese Kyowa Hydroponic System is to overcome the disadvantages present in conventional field cultivation which are restrictions of plant root growth by not only nutritional factors but also physical factors, which includes mechanical obstacles due to the presence of soil. In the system, a nutrient solution containing a suitable composition of inorganic salts is used. The solutions which is kept flowing at a certain rate with a depth of about 8cm provides the root system with an ideal environment conditions. The growth of the root system is tremendous up to the point that it is difficult to differentiate between the main and lateral roots, forming a mat-like multi-layer of roots in the container. With ideal root growth and hence ideal nutritional supply, the shoot growth and fruits productivity are increased tremendously. This huge plant productivity can be achieved by the Kyowa System, which requires no special cultivation techniques. However, one of the main shortcomings of the Kyowa System is its high capital cost. Thus, an attempt was made to modify the system in order to reduce both the capital and operating costs. The modified system retains most of the main features of the Kyowa System and incorporates the use of local materials as much as possible. The technical and economic suitability of the modified system under the Malaysian conditions are discussed in this paper.